Role of GRP78 inhibiting artesunate-induced ferroptosis in KRAS mutant pancreatic cancer cells - Wang K; Zhang Z; Wang M; Cao X; Qi J; Wang D; Gong A; Zhu H (Dove Medical Press, 2019)
Kang Wang,1,* Zhengyang Zhang,1,* Ming Wang,1 Xiongfeng Cao,1 Jianchen Qi,1 Dongqing Wang,1,2 Aihua Gong,3 Haitao Zhu1,21Central Laboratory of Medical Imaging, Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People’s Republic of China; 2Department of Radiology, Affiliated Hospital of Jiangsu University, Zhenjiang 212001, People’s Republic of China; 3School of Medicine, Jiangsu University, Zhenjiang 212013, People’s Republic of China*These authors contributed equally to this workObjective: To investigate the exact role of GRP78 in artesunate-induced ferroptosis in KRAS mutant pancreatic cancer cells.Methods: Artesunate-induced KRAS mutant human pancreatic cancer cells (AsPC-1 and PaTU8988) ferroptosis was confirmed by fluorescent staining experiments and CCK8. Western blot and short-hairpin RNA-based knockdown assays were conducted to detect GRP78 activity and its role in artesunate-induced ferroptosis.Results: Artesunate induced AsPC-1 and PaTU8988 cell death in ferroptosis manner, rather than necrosis or apoptosis. In addition, artesunate increased the mRNA and protein levels of GRP78 in a concentration-dependent manner in AsPC-1 and PaTU8988 cells. Knockdown GRP78 enhanced artesunate-induced ferroptosis of pancreatic cancer cells in vitro and in vivo.Conclusion: Combining artesunate with GRP78 inhibition may be a novel maneuver for effective killing of KRAS mutant pancreatic ductal adenocarcinoma cells.Keywords: ferroptosis, GRP78, artesunate, pancreatic cancer